In situ preparation and properties of sulfonic and phosphonic acid substituted polyphosphazene/polyaniline composites. (25th July 2016) - Hacıvelioğlu, Ferda; Kılıç, Nazmiye; Çelebi, Elif Büşra; Yeşilot, Serkan
Abstract: The first examples of polyaniline/polyphosphazene conducting composites with different ratios of the sulfonic or phosphonic acid functional polyphosphazenes and aniline were prepared in water via chemical oxidation of aniline with ammoniumperoxydisulfate by using in situ polymerization method. The novel conducting composites have been characterized by standard spectroscopic techniques; 1 H and 31 P NMR, FT-IR, and UV–vis spectroscopy. SEM and XRPD technics were used to investigate the surface and film properties and conductivity of the resulting polymer composites were investigated by four-point probe. Thermal behaviours and redox properties were also investigated by DSC, TGA and CV measurement. Graphical abstract: A series of new composites of acid substituted polyphosphazenes with different feed ratio of aniline were synthesized via chemical oxidation and properties discussed in detail. Highlights: First examples of polyaniline/polyphosphazene conducting composites were prepared. Novel composites have been characterized by standard spectroscopic techniques. Thermal, morphologic, redox and conductivity properties were investigated. Solubility and conductivity of the composites are superior than PANI.